The effect of project-based learning on improving students' science learning outcomes to privat school - Harahap, Nurtuana; Hasibuan, Rosmidah; Harahap, Risma Delima (Jurnal Mangifera Edu, 2025)
There is still a lack of creativity and innovation in teachers when selecting learning models, so students are less active in learning, and their learning outcomes are low. This study aims to analyze the project-based learning model on the science learning outcomes of students at private junior high school Bhayangkari 3 Rantauprapat in the 2024/2025 academic year. The research design used in this study is an experimental research type with the One-Group Pretest-Posttest model. Before administering treatment, a pretest is conducted to assess the group's initial stability and condition, ensuring clarity before proceeding with the intervention. After the clarity of the group's condition can be seen, then treatment is provided using a project-based learning model. The study results showed that the language of students who previously did not understand and were less active in the learning process became more active. Students can construct their understanding through groups and individuals in learning materials. After using the project-based model, the average value was 75,00, while the conventional one was 67,411. This shows a positive influence on science learning outcomes in the application of the project-based model. This also indicates that active learning strategies foster student engagement and improve academic performance.